(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The study was formulated to analyze the health benefits and antifungal and anthelmintic properties of Alstonia scholaris, specifically its bark, as claimed in Mizo traditional medicine. Biochemical assays were set up to evaluate the antioxidant potential and bioactivity tests on activity against pathogenic fungi and helminth parasites. Materials and Methods: Alstonia scholaris bark extract was prepared in petroleum ether, a non-polar solvent. Phytochemical detections were performed for 11 chemical tests. The total antioxidant, flavonoid, and phenol contents were determined. The free radical-scavenging reactions were determined using 2,2-diphenyl-1-picrylhydrazine (DPPH) scavenging and ferric ion-reducing antioxidant power (FRAP) assays. The antifungal activity was tested by an agar diffusion method. Anthelmintic activity was assessed by survival assay, scanning electron microscopy, and histology. Results: Phytosterols were identified as the main bioactive compounds. The total antioxidant was estimated at 6.4305 mg ascorbate equivalent per gram, flavonoid at 128.03 mg gallic acid equivalent per gram, and phenol at 10.72 mg pentahydroxyflavone equivalent per gram. The FRAP assay demonstrated a concentration-dependent scavenging of ferric (Fe⁺³) cations. The DPPH scavenging reaction showed the half-maximal inhibitory concentration at 136 µg/ml. It was found that the plant extract was effective against Candida albicans, Neocosmospora keratoplastica, and Neosartorya fumigata, with the highest degree of inhibition against C. albicans. It exhibited activity against the poultry tapeworm, Raillietina echinobothrida. Light and electron microscopy revealed signature antiparasitic effects on different parts of the parasite body. Conclusion: The study vindicated the medicinal properties of A. scholaris in terms of antioxidants, antifungal, and antiparasitic activities. J. Adv. Vet. Anim. Res., 12(4): 1333–1344, December 2025 http://doi.org/10.5455/javar.2025.l993